2008
DOI: 10.1111/j.1365-2591.2008.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of nickel‐titanium rotary endodontic instruments in simulated clinical conditions: a computational study

Abstract: The most demanding working conditions were observed in canals with sharp curves, especially in areas where the instruments had larger diameters. To prevent possible damage to instruments and fracture, it is advised that the instruments should be discarded following their use in such canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
4
32
1
1
Order By: Relevance
“…In all the endeavors to perform analysis on the apical third, it was not possible to keep the probe on a plane to scan an area. Nevertheless, this fact does not invalidate the final result obtained, mainly because, according to Necchi et al (2008), using an finite element model for the study of rotary instruments, observed that the greatest demand on the working conditions occurs in canals with the presence of curvatures with an angle equal to or greater than 408, especially in areas in which the caliber of the instrument diameter is larger, as is the case in the cervical region of any rotary instrumentation system.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In all the endeavors to perform analysis on the apical third, it was not possible to keep the probe on a plane to scan an area. Nevertheless, this fact does not invalidate the final result obtained, mainly because, according to Necchi et al (2008), using an finite element model for the study of rotary instruments, observed that the greatest demand on the working conditions occurs in canals with the presence of curvatures with an angle equal to or greater than 408, especially in areas in which the caliber of the instrument diameter is larger, as is the case in the cervical region of any rotary instrumentation system.…”
Section: Discussionmentioning
confidence: 92%
“…Some authors have used a mathematical finite element model (Kim et al, 2009;Necchi et al, 2008) or AFM (Inan et al, 2007b;Topuz et al, 2008;Valois et al, 2005Valois et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…the stress distribution) and predict the most likely to be location for crack growth. This is very difficult to assess through laboratorial or in vivo tests [17].…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of these stresses is also related to arc length and instrument size [18]. To Lopes et al [18], the radius and the position of the canal curvature are the most critical parameters that determined the stress in the instrument, with higher stress levels being produced by decreasing the radius and moving from the apical to the mid root position [19]. Cumulative microstructural changes eventually cause the instrument to fracture [17].…”
Section: Instrument Failure Ratementioning
confidence: 99%